Pertumbuhan dan Perkembangan Anak Usia 3-6 Tahun - Meiuta Hening Prastiwi (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
The purpose of this study was to determine the picture of the growth and development of children aged 3-6 years in Pertiwi Metro City PAUD. This research method is descriptive, with a sample of 120 people, from playgroups, TK A and TK B PAUD Pertiwi Metro City. The sampling technique used is randomization. Results showed that almost all children had good nutritional status, which was 95%, 96.66% of children had normal head circumference, almost all (96.23%) child development was appropriate, 98.73% of children had normal vision, 97, 5% of children have normal hearing power. Nearly all (94.17%) of children have normal emotional behavior problems, and 95.83% of children do not experience the possibility of impaired concentration and hyperactivity. Conclusions looking at the results of this study are suggested that educational institutions work together with puskesmas, to detect early deviations of child development in a continuous, continuous manner, and are expected to be a reference for other schools in the school health business program (UKS) because PAUD Pertiwi Metro City has become national level UKS champion.